Description of the system of tasks for gradual learning the Kazakh language - Koshanova Ж.Т.; Akhmetova Т. А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article analyzes the system of tasks aimed at the level mastery of the Kazakh language on the basis of the Model curriculum of the general education cycle for higher and postgraduate educational institutions, for students studying in non-linguistic specialties. The article also reflects the requirements for reproductive, variative, research, creative tasks in teaching the Kazakh language and their detailed description is given. Tasks are selected in accordance with the types of speech activity (speaking, listening, reading, writing, communication). The main purpose of the article is to analyze the work of scientists from a scientific and theoretical point of view, to identify and systematize the types of tasks, based on the content of each activity, to study and demonstrate skills aimed at effectively teaching the Kazakh language: working with a dictionary, building diagrams, drawing up abstracts on a specific topic , compiling comparative charts and graphs, working with literature, holding discussions, holding debates (reflections, discussions), holding a round table, etc. In addition, the results of the development and use of the task system developed in the process of teaching the Kazakh language are investigated, thereby revealing the scientific and methodological significance of the article. A thoughtfully designed system of tasks creates an opportunity to form the linguistic competencies of students, to fully master all types of speech activity (speaking, listening, reading, writing, communication) in the process of learning the Kazakh language.